Effects of temperature, proportion and organic loading rate on the performance of anaerobic digestion of food waste - Blasius, Jandir Pereira [UNESP]; Contrera, Ronan Cleber; Maintinguer, Sandra Imaculada [UNESP]; Alves de Castro, Marcus Cesar Avezum [UNESP] (Elsevier, 2020)
In Brazil, a significant amount of organic waste is produced in households and restaurants. This study thus aimed to determine the ideal conditions for generating methane from the treatment of household waste by anaerobic digestion, under mesophilic (37 °C) and thermophilic (55 °C) conditions, to determine the maximum organic loading rate (OLR) in the reactors, and to evaluate kinetic parameters by statistical models: Modified Gompertz, First-Order, Logistic and Transference functions. The experiments were conducted in anaerobic batch reactors. Different proportions of pre-prepared waste (PPW)/leftover waste (LW) were used: 100/0, 75/25, 50/50, 25/75, and 0/100 and different ORL: 0.15; 0.30; 0.45; 0.60; and 0.90 g TVS (Total Volatile Solids).L−1.d−1. For both conditions, the optimal proportions of PPW/LW were 100/0 and 75/25 %. Under mesophilic condition, the best results were observed (869 mL of CH4.g TVS−1). The maximum organic load was 0.30 g TVS.L−1.d−1. The best data adjustment was performed by the Transference function.
Keywords: Biochemical methane potential; Kinetic models; Leftover waste; Organic waste treatment; Pre-preparation waste